Helicobacter pylori colonization and pregnancies complicated by preeclampsia, spontaneous prematurity, and small for gestational age birth. Issue 2 (27th October 2016) - den Hollander, Wouter J.; Schalekamp‐Timmermans, Sarah; Holster, I. Lisanne; Jaddoe, Vincent W.; Hofman, Albert; Moll, Henriëtte A.; Perez‐Perez, Guillermo I.; Blaser, Martin J.; Steegers, Eric A. P.; Kuipers, Ernst J.
Abstract: Background: Preeclampsia (PE), small for gestational age (SGA), and spontaneous preterm birth (PTB) each may be complications of impaired placental function in pregnancy. Although their exact pathogenesis is still unknown, certain infectious agents seem to play a role. Helicobacter pylori (H. pylori) colonization has been associated with increased risk for PE. Our aim was to assess the association between H. pylori colonization and PE, SGA, and PTB. Material and Methods: We measured IgG anti‐ H. pylori and CagA antibodies in serum of pregnant women (median 20.5 weeks, range 16.5‐29.4) who participated in a population‐based prospective cohort study. Delivery and medical records were assessed. Information on demographics, education, and maternal risk factors was collected by questionnaire. We used multivariate logistic regression analyses to assess associations between H. pylori colonization and PE, SGA, and PTB. Results: In total, 6348 pregnant women were assessed. H. pylori positivity was found in 2915 (46%) women, of whom 1023 (35%) also were CagA‐positive. Pregnancy was complicated by PE, SGA, or PTB in 927 (15%) women. H. pylori colonization was associated with PE (aOR 1.51; 95%CI 1.03‐2.25). Differentiation according to CagA status revealed the same risk. H. pylori was positively related with SGA, mainly explained by CagA‐positive strains (aOR 1.34; 1.04‐1.71). No association was observed between H. pylori and PTB. Conclusions: Our data suggest that H. pylori colonization may be a risk factor for PE and SGA. If these associations are confirmed by future studies and shown to be causal, H. pylori eradication may reduce related perinatal morbidity and mortality.